Recovery of green turtle populations and their interactions with coastal dune as a baseline for an integral ecological restoration - Guzmán-Hernández, Vicente; del Monte-Luna, Pablo; López-Castro, Melania C.; Uribe-Martínez, Abigail; Huerta-Rodríguez, Patricia; Gallegos-Fernández, Sandra A.; Azanza-Ricardo, Julia; Martínez-Portugal, Rosa C.; Barragán-Zepeda, Ana K.; Quintana-Pali, Guadalupe P.; Martín-Viaña, Yanet F.; Gómez-Ruíz, Pilar A.; et al. (Instituto de Ecología, A.C., 2022)
Background and Aims: Ecological restoration has focused on the physical and vegetation components of ecosystems, leaving aside studies on wild fauna and their interactions. Chelonia mydas is an endangered macroherbivore that nests on sandy beaches of Mexico and Cuba, and influences the coastal vegetation with organic matter contributions. The objectives of this study were to analyze its population recovery, a greenness index for dune vegetation, and the amount of organic matter estimated from its clutches before and after the implementation of an official Mexican norm. Methods: Biological data obtained from two and three decades of monitoring 16 Chelonia mydas nesting beaches were analyzed; based on these, three levels of demographic indexes were carried out, the contribution of organic matter by marine turtles to the beach and the vegetal vigor using remote sensing, besides implementing the pertinent statistical analysis. Key results: There was an exponential increase of the green turtle nests (between 12 and 14% per year), associated with population recruitment pulses in 2000 and 2008. The contribution of organic matter to the beach was significantly higher after a change in clutches management in Mexico, and an increase in the dune vegetation greenness was detected in high Chelonia mydas nesting zones. Conclusions: The increase of the green turtle populations invites to reflex about the implications of the recovery of species of fauna have on other communities in the ecosystems they inhabit, demanding the analysis of the actual paradigms and the adaptation strategies that attend their management needs, procuring the ecological integrity conditions of their habitats.